Qualitative analysis of the capacity to consent to treatment in patients with a chronic neurodegenerative disease: Alzheimer’s disease / Analisi qualitativa sulla capacità a prestare consenso al trattamento in pazienti con malattie cronico degenerative neuropsicoorganiche: Demenza di Alzheimer - Carabellese, Felice; Felthous, Alan R; La Tegola, Donatella; Piazzolla, Giuseppina; Distaso, Salvatore; Logroscino, Giancarlo; Leo, Antonio; Ventriglio, Antonio; Catanesi, Roberto (International journal of social psychiatry, 2018)
Objective: Informed consent is an essential element in doctor–patient relationship. In particular, obtaining valid informed consent from patients with neurocognitive diseases is a critical issue at present. For this reason, we decided to conduct research on elderly patients with Alzheimer’s disease (Diagnostic and Statistical Manual of Mental Disorders, 5th Edition (DSM-5) to assess their capacity to make treatment decisions. Methods: The experimental group comprised 70 Alzheimer patients who were admitted to the Neurodegenerative Disease Unit of the University of Bari. The control group consisted of 83 elderly patients without neurocognitive disorders who were hospitalized in the Geriatric Unit at the same university. After providing written consent to participate in the research, each subject underwent the following assessments: (a) assessment of comprehension sheet, (b) Neuropsychiatric Inventory (NPI) and Global Functioning Evaluation (GFE), (c) neurological evaluation, (d) neuropsychological assessment with a full battery of tests, (d) The MacArthur Treatment Competence Study (MacArthur Competence Assessment Tool for Treatment (MacCAT-T); understanding, appreciating, reasoning and expressing a choice) and (e) a semi-structured interview administered by the patient’s caregiver. Results/conclusion: The present survey was designed to analyze possible qualitative and quantitative correlations between cognitive functioning and capacity to consent in relation to different degrees of severity of the neurodegenerative disorder. A large portion of the patients in our experimental sample did not appear to have the capacity to provide a valid consent. The authors present initial results of this study and discuss their possible implications.